An autoactive NB-LRR gene causes Rht13 dwarfism in wheat - Borrill, Philippa; Mago, Rohit; Xu, Tianyuan; Ford, Brett; Williams, Simon J; Derkx, Adinda; Bovill, William D; Hyles, Jessica; Bhatt, Dhara; Xia, Xiaodi; MacMillan, Colleen; White, Rosemary; et al. (Proceedings of the National Academy of Sciences of the United States of America, 2022)
Semidwarfing genes have greatly increased wheat yields globally, yet the widely used gibberellin (GA)-insensitive genes Rht-B1b and Rht-D1b have disadvantages for seedling emergence. Use of the GA-sensitive semidwarfing gene Rht13 avoids this pleiotropic effect. Here, we show that Rht13 encodes a nucleotide-binding site/leucine-rich repeat (NB-LRR) gene. A point mutation in the semidwarf Rht-B13b allele autoactivates the NB-LRR gene and causes a height reduction comparable with Rht-B1b and Rht-D1b in diverse genetic backgrounds. The autoactive Rht-B13b allele leads to transcriptional up-regulation of pathogenesis-related genes including class III peroxidases associated with cell wall remodeling. Rht13 represents a new class of reduced height (Rht) gene, unlike other Rht genes, which encode components of the GA signaling or metabolic pathways. This discovery opens avenues to use autoactive NB-LRR genes as semidwarfing genes in a range of crop species, and to apply Rht13 in wheat breeding programs using a perfect genetic marker.
Keywords: Dwarfism; autoactive NB-LRR; nanismus; reduced-height (Rht) gene; šlechtění rostlin; vazebná místa; nukleotidy; rostlinné proteiny; Triticum aestivum L. (wheat); semidwarfing gene; Plant Proteins; pšenice; Triticum; Binding Sites; Plant Breeding; Nucleotides